2009
DOI: 10.1158/0008-5472.can-08-4282
|View full text |Cite
|
Sign up to set email alerts
|

KLF6-SV1 Is a Novel Antiapoptotic Protein That Targets the BH3-Only Protein NOXA for Degradation and Whose Inhibition Extends Survival in an Ovarian Cancer Model

Abstract: Defects in apoptosis are not only a hallmark of cancer initiation and progression but can also underlie the development of chemoresistance. How the tightly regulated cascade of protein-protein interactions between members of three competing protein families regulating the apoptotic cascade is subverted in tumor cells is incompletely understood. Here, we show that KLF6-SV1, whose overexpression is associated with poor survival in several different cancers and is an alternatively spliced isoform of the Krüppel-l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…The overall integrity of the mitochondrial function is controlled by the Bcl-2 family of proteins that includes both anti-apoptotic (Bcl-2, Bcl-XL, and Mcl-1) and proapoptotic members (Bax, Bak, Noxa, and p53 upregulated modulator of apoptosis (PUMA)) [31,32,[39][40][41]. Previous reports have demonstrated that the targeted reduction of KLF6-SV1 resulted in marked activation of the intrinsic pathway of apoptosis through upregulation of the pro-apoptotic Noxa and degradation of the anti-apoptotic Mcl-1 in lung, prostate, and ovarian cancer cell lines [10,24,26]. Here, we also confirmed that the expressions of Noxa and Mcl-1 could be regulated by KLF6-SV1 siRNA in gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The overall integrity of the mitochondrial function is controlled by the Bcl-2 family of proteins that includes both anti-apoptotic (Bcl-2, Bcl-XL, and Mcl-1) and proapoptotic members (Bax, Bak, Noxa, and p53 upregulated modulator of apoptosis (PUMA)) [31,32,[39][40][41]. Previous reports have demonstrated that the targeted reduction of KLF6-SV1 resulted in marked activation of the intrinsic pathway of apoptosis through upregulation of the pro-apoptotic Noxa and degradation of the anti-apoptotic Mcl-1 in lung, prostate, and ovarian cancer cell lines [10,24,26]. Here, we also confirmed that the expressions of Noxa and Mcl-1 could be regulated by KLF6-SV1 siRNA in gastric cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that KLF6-SV1 was an important anti-apoptosis protein in some tumors [26]. (Fig.…”
Section: Klf6-sv1 Sirna Enhances the Apoptosis Of Gastric Cancer Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…iv. Inhibition of KLF6-SV1 by RNAi in prostate carcinoma and ovarian cancer cell lines (41,47). v. Overexpression of KLF6-SV2 in immortalized human hepatocytes and HepG2 cell line (40).…”
Section: Klf6 Function In Cellmentioning
confidence: 99%